Al-Rashid, Imad al-Din. “Textual Criticism in the Sciences of Fiqh and Hadith,” Year 10, Issue 39 (Winter 1426 AH/ 2005 CE), Pp. 75-102. - الرشيد عماد الدين (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2005)
Imad al-Din al-Rashid’s article treats the concept of textual criticism, explaining its dimensions and boundaries in light of similar concepts. It attempts to demonstrate the commonalities of the Shariʿah sciences, such as the sciences of uṣūl al-fiqh and hadith, in their sources and methodologies. It also discusses the notions of a fiqh perspective and a hadith perspective. The article maintains that both, the unity of the Shariʿah sciences and the notion of fiqh and hadith perspectives, have deep implications on Shariʿah knowledge that transcend the boundaries of textual criticism. The article defines, moreover, the concept of textual criticism, and describes its types and the sciences that are instrumental for it.